THE EFFECT OF ACUPRESSURE AND EFFLEURAGE ON PAIN RELIEF IN THE ACTIVE PHASE OF THE FIRST STAGE OF LABOR IN THE COMMUNITY HEALTH CENTER OF KAWUNGANTEN, CILACAP, INDONESIA - Yuli Sya’baniah Khomsah; Agus Suwandono; Ida Ariyanti (Belitung Nursing Journal, 2017)
Background: Pain during pregnancy and childbirth is a physiological process, but it leads to discomfort without pain management. Acupressure and effleurage are considered to be effective in reducing labor pain. Objective: To examine the effect of acupressure and effleurage in reducing pain during in the active phase of the first stage of labor in the Community Health Center of Kawunganten, Cilacap, Central Java, Indonesia. Methods: This was a quasi-experimental study with pretest-posttest control group design. There were 33 respondents recruited using simple random sampling. Numerical rating scale was used to measure labor pain. Data were analyzed using one-way ANOVA, post hoc ANOVA and repeated ANOVA for normal data distribution. Kruskal Wallis was also used for non-normal data distribution. Results: There was a statistically significant mean difference of pain scale before and after given acupressure and effleurage (p-value <0.05). However, acupressure treatment had a greater effect in reducing pain compared with effleurage. Conclusion: Acupressure and effleurage had a significant effect in reducing pain in mothers in the active phase of the first stage of labor. The results of this study are expected to enrich and contribute to the development of science in the field of health promotion, and serve as an additional input for midwives in order to carry out the care of mother during labor.